REGIONAL LEVEL ANALYSIS OF OPEN GOVERNMENT DEVELOPMENT IN GEORGIA ON THE EXAMPLE OF THE AUTONOMY OF AJARA (International Journal of Innovative Technologies in Economy, 2023)
Georgia has been a member of the "Open Government Partnership" since 2011 and from the day of joining, has been a leading and active member of the international platform with achievements at the governmental, parliamentary, and local self-government levels. The next logical step is the membership of Ajara as a region in the partnership, so it was considered necessary to study the current situation in the executive branches of Ajara in the direction of open governance and gather the information that would further help us prepare recommendations in terms of strengthening open governance in the Ajara region.Depending on the purpose of the research problem and research questions, the research included several methods of data collection: In particular, the official websites of the executive agencies of the region were studied, the social network platforms of agencies were monitored, an analysis of the completeness and quality of published data sets, information requests in different forms and thoughtful evaluation of responses to requests. The paper is also based on all the materials received and used by the Supreme Council of the Autonomous Republic of Ajara within the framework of the thematic research.